2020
DOI: 10.1002/hpja.341
|View full text |Cite
|
Sign up to set email alerts
|

An overview of digital and online strategies to reduce gambling harm

Abstract: Issue addressed Advancements in mobile‐ and web‐based technologies proliferate everyday opportunities to gamble. The increased availability, popularity and intensity of online gambling platforms and interactive gaming activities also changes the way we construct gambling harm reduction interventions. Information and communication technologies (ICT) provide potential opportunities to reduce harm from online gambling through harm minimisation initiatives and currently available services. The aim of this review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A solid body of research shows that population-level, universal, actions are the most effective in gambling as well as in other sectors [e.g. 15 , 80 , 88 , 6 89 . Yet, harm prevention and reduction action need to also include selective and indicated measures to help those who have already been or are at risk of being afflicted by gambling harms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A solid body of research shows that population-level, universal, actions are the most effective in gambling as well as in other sectors [e.g. 15 , 80 , 88 , 6 89 . Yet, harm prevention and reduction action need to also include selective and indicated measures to help those who have already been or are at risk of being afflicted by gambling harms.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic interventions in online environments include approaches such as web-based psychotherapy or counselling, and online support forums [ 80 ]. The characteristics of treatment interventions in online environments have already received some research attention [ 22 , 80 ], with most research focussing on computer-assisted or online therapy programmes for disordered gambling. Overall, studies have shown mixed results.…”
Section: Indicated Interventionsmentioning
confidence: 99%
“…Only one study reported on a military population 79 , however this was a systematic review of existing literature. One examined study found that individuals would be quickly reprimanded for gambling, but meaningful assistance was slow to come, whereas another found that 21/25 active personnel who received treatment were retained in the military, compared to the 4 who lost their jobs.…”
Section: Military Personnelmentioning
confidence: 99%
“…Only one study reported on a military population 76 , however this was a systematic review of existing literature.…”
Section: Military Personnelmentioning
confidence: 99%